Cynara cardunculus L. flowers enzymatic profiles and ewe’s cheese yield - Fonseca, Ana (2022)
Cynara cardunculus L. flowers have been used, in the form of an aqueous extract as vegetable coagulant, in the production of Protected Designation of Origin (PDO) ewe’s cheeses in the Mediterranean Basin. The presence of aspartic proteases, cardosins, promote specific proteolysis in milk coagulation and cheese ripening. Nine aspartic proteinases have been identified in C. cardunculus flower extracts, which have been assigned different names, cardosins A–H 1. Cardosins A and B specifically proteolyze at the surface of casein micelles in the early phases of milk coagulation. Cardosin A has a high specific proteolytic action on K-casein resulting in less softer textures, whereas cardosin B has a low proteolytic action on K-casein, and a higher non-specific proteolytic action responsible for nonfirm inner cheese texture 1. Lower ratios between specific milk clotting activity and the non-specific enzymatic proteolytic coagulant activity have been associated to lower cheese yields 2. In the present work, we evaluated the influence of the extract of flowers from two individual C. cardunculus plants (Cyn_AB, presence of cardosina A, clearly predominant, and cardosin B; Cyn_B, presence of cardosin B and absence of the typical cardosin A) on ewe cheesemaking parameters and cheese yield. The characterization of the cardosin profiles was confirmed by native-PAGE (12,5%), a technique that allows the distinction of the presence or absence of the typical cardosin A. Milk-clotting activity (MCA) was accessed by visual observation according to ISO 23058/IDF 199 (ISO/IDF, 2006). The ewe’s cheeses were manufactured in artisanal cheese manufacturer in Serpa, Portugal. Physicochemical parameters of milk and whey were evaluated, time to curd firmness (CF) was registered and the cheese yield accessed during the 30 days ripening time. The main results showed that the initial cheese yield (kg/L) per treatment differed, but there were no differences at the end of the ripening period, suggesting that the enzymatic profile of C. cardunculus flowers does affect the cheese yield.